Development and application of a sensitive, phenotypic, high-throughput image-based assay to identify compound activity against Trypanosoma cruzi amastigotes - Sykes, Melissa L. (Int J Parasitol Drugs Drug Resist, 2015)
We have developed a high content 384-well, image-based assay to estimate the effect of compound treatment on Trypanosoma cruzi amastigotes in 3T3 fibroblasts. In the same well, the effect of compound activity on host cells can also be determined, as an initial indicator of cytotoxicity. This assay has been used to identify active compounds from an in-house library of compounds with either known biological activity or that are FDA approved, and separately, from the Medicines for Malaria Venture Malaria Box collection. Active compounds were screened against T. cruzi trypomastigotes, utilising an assay developed with the viability dye resazurin. Twelve compounds with reconfirmed solid sample activity, with IC(50) values of less than 10 μM and selectivity indices to T. cruzi amastigotes over 3T3 host cells of between >22 and 319 times were identified from these libraries. As 3T3 cells are contact inhibited, with limited proliferation in the assay, selective compounds of interest were profiled in a separate assay to estimate the viability of compound treated, replicating HEK293 cells. Selective compounds that were not previously reported in the literature were further profiled by extending the incubation time against amastigote infected 3T3 cells to determine if there were residual amastigotes post-treatment, important for the consideration of the exposure time required for further biological characterisation. The assay development process and the suitability of identified compounds as hit molecules for Chagas disease research are discussed.